Increased knowledge of the effects of smoking and second-hand smoke encourages smoke-free homes. (August 2014) - Fenton, Brenda; Thankappan, Kavumpurathu Raman; Champagne, Beatriz; Lv, Jun; Anthony, Denis
Objective: To establish the drivers for smoke-free homes among current daily smokers. Design: A cross-sectional study employing interviews (adults) and self-completed surveys (schoolchildren). Sample: Children aged 12 and 14 in schools in four cities in China, India, Mexico and England. Adults in the community. Measurements: Knowledge, attitude, beliefs and behaviour relevant to second-hand smoke in home. Intervention: None. Results: A total of 8994 adults and 14, 756 children were surveyed. Knowledge of some of the effects of tobacco is high, but other effects are poorly understood in all cities. In Thiruvananthapuram, there is a lack of awareness of the addictiveness of tobacco, and Hangzhou has poor knowledge in general. Conclusions: Messages about reducing tobacco usage are effective in support of smoke-free homes in the city with poorest knowledge (Hangzhou) but other factors are more important where knowledge is high.